Research on Automatically Correlation Technology of Virtual Terminals in Intelligent Substation Based on Standard Function Coding. Issue 1 (1st November 2022) - Chen, Pan; Xiao, Zhihong; Yan, Peili; Feng, Teng; Wang, Xiaoming; Wang, Liang
Abstract: The virtual terminals correlation is one of the main contents of the secondary system design in intelligent substations. The traditional manual method of virtual terminals correlation has a large workload and a high error rate. To improve efficiency and accuracy, we proposed a virtual terminals automatically correlation technology based on standard function coding. By coding the external function loop of the secondary device, the standard virtual terminals which are independent of the manufacturers are obtained. And then referring to the standard virtual terminals associating template library, the automatic correlation of the virtual terminals of secondary devices could be completed. The proposed method can effectively solve the problem that the definition of virtual terminals is difficult to unified among the domestic manufacturers, and significantly improve the matching rate of the virtual terminals automatically correlation.